ASPEK PERFORMATIF DAN INFOMATIF HADIS DALAM FILM ANIMASI NUSSA EPISODE BUKAN MAHRAM - Najibur Rohman; Khotibul Umam, Rohman, Junaidi, Fatichatus Sa’diyah (ADISAM PUBLISHER, 2024)
This research is motivated by the rampant behaviour of ‘shaking hands’ which is increasingly being done by humans. Hand-shaking behaviour is a way of dressing people that is not as usual to look different with the aim of attracting the attention of others and acting arrogant. This handshaking behaviour is a behaviour that is disliked by the Prophet (SAW) and it is even mentioned that Allāh SWT threatens to dress the perpetrators of shaking hands in the world in clothes of humiliation in the hereafter. This research refers to identifying the object of reception in terms of informative and performative functions. Hadith Shuhrah in the film